2009
DOI: 10.5962/bhl.title.142854
|View full text |Cite
|
Sign up to set email alerts
|

Phyllostomid bats of Colombia : annotated checklist, distribution, and biogeography

Abstract: We report 118 confirmed phyllostomid species for Colombia, and 14 species po¬ tentially present in the country, for a total of 132 species representing 40 genera and 10 subfamilies. All known phyllostomid subfamilies are represented in Colombia, with the exception of the subfamily Macrotinae (not present in South America). At 118 known species, Colombia has the greatest number of phyllostomid bats of any country. Included in the lists are 27 recently recognized species (19 newly described species and eight new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
19

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 28 publications
0
30
1
19
Order By: Relevance
“…Although MarinhoFilho and Sazima (1998) reported 19 endemic species for Brazil (14% of the bat fauna recorded in that time), most of these bats occur in other countries, and nowadays only 10 species can be recognized as endemic (Table 1). The rate of Brazilian bat endemism (5%) is, therefore, higher than that recorded for Venezuela (2.4%; Sánchez and Lew 2012) and Colombia (2.6%; Alberico et al 2000;Mantilla-Meluk et al 2009;Solari et al 2013), but still close to that found in Peru (4.2%; Pacheco et al 2009). These data are suggestive of hidden bat diversity still to be discovered in Brazil.…”
Section: Discussionmentioning
confidence: 63%
“…Although MarinhoFilho and Sazima (1998) reported 19 endemic species for Brazil (14% of the bat fauna recorded in that time), most of these bats occur in other countries, and nowadays only 10 species can be recognized as endemic (Table 1). The rate of Brazilian bat endemism (5%) is, therefore, higher than that recorded for Venezuela (2.4%; Sánchez and Lew 2012) and Colombia (2.6%; Alberico et al 2000;Mantilla-Meluk et al 2009;Solari et al 2013), but still close to that found in Peru (4.2%; Pacheco et al 2009). These data are suggestive of hidden bat diversity still to be discovered in Brazil.…”
Section: Discussionmentioning
confidence: 63%
“…Nosotros revisamos todos los especímenes disponibles de V. nymphaea del ICN y no encontramos ningún ejemplar procedente de Charalá, por lo que el registro de Otálora-Ardila (2003) debe corresponder a una identificación de campo errónea. Mantilla-Meluk et al (2009) presentaron un modelo de distribución potencial de V. nymphaea en Colombia, que restringe la especie al sur de la Amazonía colombiana; aparentemente este es un error en los títulos de los mapas ya que en el cuadro resumen de la distribución aparece que la distribución de V. nymphaea está restringida para la región Pacífico (Mantilla-Meluk et al 2009). Para el valle medio del Río Magdalena, hay un registro publicado de V. nymphaea procedente de Totare (2400 m), departamento del Tolima, depositado en la Colección Zoológica, Universidad del Tolima-Mastozoología CZUT-M (CZUT-M 0737) (Galindo-Espinosa et al 2011), pero al revisar una imagen del cráneo del espécimen pudimos verificar que correspondía a un Dermanura cf.…”
Section: Resultsunclassified
“…These specimens match the following characters in L. occidentalis re-description (Velazco and Cadenillas 2011): mastoid process developed; clinoid processes laterally curved; cingula absent on upper canines; distal accessory cusp on P3 and P4 present; labial cingula on P4 absent; mesostylar crest on M1 and M2 present, and lingual cingula on M1 and M2 present (Figure 3). Prior Velazco and Cadenillas (2011), it was difficult to define the northern limits of L. s. occidentalis and this is probably the reason for which the taxon was not reported for the western portion of the country in recent checklists (Alberico et al 2000;Mantilla-Meluk and Jiménez-Ortega 2006;Mantilla-Meluk et al 2009). As mentioned above, Colombian L. occidentalis match all cranial characters in Velazco and Cadenillas (2011) re-description of the species.…”
Section: Resultsmentioning
confidence: 99%